In-hospital outcomes of catheter-directed thrombolysis in patients with pulmonary embolism. Issue 3 (25th November 2020) - Hobohm, Lukas; Schmidt, Frank P; Gori, Tommaso; Schmidtmann, Irene; Barco, Stefano; Münzel, Thomas; Lankeit, Mareike; Konstantinides, Stavros V; Keller, Karsten
Abstract: Aims: Catheter-directed treatment of acute pulmonary embolism (PE) is technically advancing. Recent guidelines acknowledge this treatment option for patients with overt or imminent haemodynamic decompensation, particularly when systemic thrombolysis is contraindicated. We investigated patients with PE who underwent catheter-directed thrombolysis (CDT) in the German nationwide inpatient cohort. Methods and results: Data from hospitalizations with PE (International Classification of Disease code I26) between 2005 and 2016 were collected by the Federal Office of Statistics in Germany. Patients with PE who underwent CDT (OPS 8-838.60 or OPS code 8-83b.j) were compared with patients receiving systemic thrombolysis (OPS code 8-020.8), and those without thrombolytic or other reperfusion treatment. The analysis was not prespecified; therefore, our findings can only be considered to be hypothesis generating. We analysed data from 978 094 hospitalized patients with PE. Of these, 41 903 (4.3%) patients received thrombolytic treatment [systemic thrombolysis in 4.2%, CDT in 0.1% (1175 patients)]. Among patients with shock, CDT was associated with lower in-hospital mortality compared to systemic thrombolysis [odds ratios (OR) 0.30 (95% 0.14–0.67); P = 0.003]. Intracranial bleeding occurred in 14 (1.2%) patients who received CDT. Among haemodynamically stable patients with right ventricular dysfunction (intermediate-risk PE), CDT also was associated with a lower risk of in-hospital mortality compared to systemic thrombolysis OR 0.55 [95% confidence interval (CI) 0.40–0.75]; P < 0.001 or no thrombolytic treatment [0.45 (95% CI 0.33–0.62); P < 0.001]. Conclusion: In the German nationwide inpatient cohort, based on administrative data, CDT was associated with lower in-hospital mortality rates compared to systemic thrombolysis, but the overall rate of intracranial bleeding in patients who received CDT was not negligible. Prospective controlled data are urgently needed to determine the true value of this treatment option in acute PE.